PENINGKATAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL PEMBELAJARAN BERMAKNA PADA MURID KELAS IV SDN NO 141 PAKKA KECAMATAN TELLULIMPOE KABUPATEN SINJAI - Mayangsari, Wulan (AIJER, 2019)
Abstract: Improving Science Learning Outcomes through the Application of Meaningful Learning Model in Class IV Students of SDN No. 141 Pakka, Tellulimpoe District, Sinjai Regency. This study aimed to determine the improvement of science learning outcomes in elementary school students through the application of meaningful learning modelin class IV students of SDN No. 141 Pakka Tellulimpoe District, Sinjai Regency. The population in this study was all IV students of SDN No. 141 Pakka Tellulimpoe District, Sinjai Regency in the academic year 2016-2017, 22 students consisted of 8 male students and 14 female students. In this study, there were two kinds of variables, namely: (1) Meaningful learning model as variable X (free), and (2) Science learning outcomes as variable Y (bound). Science learning outcomes were measured using cycle tests, and student activities were measured using observation sheets. Science learning outcomes of class IV students of SDN No. 141 Pakka Tellulimpoe District, Sinjai Regency in the first cycle obtained the highest value was 75, the lowest value was 40, and an average value was 49.31, out of the 22 students who took the learning outcomes test in the first cycle there were 17 students or 77.27% of students who had uncompleted yet, and 5 students or 22.72% of students who had finished while in the second cycle the highest score was 100, the lowest score was 80, the range of scores was 20 and the average score was 89.31% of 22 students who took the learning outcomes test in the second cycle, all students were 22 students or 100% of students who had finished. Thus, this study had proved that if the learning model was meaningfully applied, the science learning of class IV students of SDN No. 141 Pakka Tellulimpoe District, Sinjai Regency increased.Keywords: Science learning outcomes, meaningful learning model.